2009
DOI: 10.1007/978-1-84882-762-2_64
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Community Response to Urban Traffic Noise

Abstract: Traffic noise is a major environmental source of pollution in the whole planet, both in developed and in developing nations. The study being reported here has been carried out on one of the most busy and crowded streets in the downtown area of Kerman, located in south east of Iran, which have heavy traffic during the day. Total of 20 measuring points were selected along the main road and its 6 connecting streets. In this study the A-weighted continuous equivalent sound level values and statistical levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…The knowledge about the effect of low-frequency noise can help readers analogy this kind of effect with the results. The obtained results are consistent with the results of other studies (41)(42)(43). The use of risk-based health impact assessment models on health such as Cox can be effective in analyzing relevant environmental data and decisions.…”
Section: Resultssupporting
confidence: 93%
“…The knowledge about the effect of low-frequency noise can help readers analogy this kind of effect with the results. The obtained results are consistent with the results of other studies (41)(42)(43). The use of risk-based health impact assessment models on health such as Cox can be effective in analyzing relevant environmental data and decisions.…”
Section: Resultssupporting
confidence: 93%
“…Noise pollution can be considered as one of the significant toxins present in urban areas. Its assessment, control, and decrease are among the major natural well-being concerns for specialists [Mohammadi, 2009;Zannin, et al, 2013]. Many researchers have also reported that road traffic is the most general and prominent noise pollution source in the developing countries [Mocuta, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…Today in many countries the issue of noise pollution among the different types of environmental pollutions has been identified as a widespread and even global problem (Barrientos et al, 2004). The World Health Organization has introduced the noise pollution in large cities as the third most dangerous pollution which is mentioned after the air and the water pollution (Mohammadi, 2009). The noise pollution is a level of sound that causes harassment, damage and provoke human.…”
Section: Introductionmentioning
confidence: 99%